Financial Performance Analysis of the Indonesian Football Club Bali United for the 2019-2023 Period Based on Profitability Ratio, Liquidity Ratio, Activity Ratio, and Solvability Ratio - Pratama, Rifki Nanda; Bhilawa, Loggar (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
Football has developed into a global industry that demands professional financial management. Bali United FC became the first football club in Indonesia to be listed on the stock exchange through an Initial Public Offering (IPO) in 2019. This study examines the trends and differences in the financial performance of Bali United from 2019 to 2023, focusing on profitability, liquidity, activity, and solvency ratios. The methods used are trend analysis, the Kruskal-Wallis test, and one-way repeated Measures ANOVA. The results show that Bali United's financial performance fluctuated due to business expansion and external factors, with improvements in 2021–2022 followed by a decline in 2023. Significant differences were found among several financial ratio indicators, but no significant differences were observed across the years as a whole. These findings serve as a valuable evaluation tool for the club in managing its finances after going public.